Model Pelayanan Kesehatan Berbasis Pelanggan (Studi Evaluasi di Bagian Unit Rawat Inap Rumah Sakit Umum Daerah Sidoarjo Jawa Timur) - Nawangsari, Ertien Rining (Jurnal Aplikasi Manajemen, 2012)
The demands of implementing high quality services have also been felt by regional generalhospitals as a health service institution owned by the local govermment. The health service are stronglydemanded to meet the public need and expectation as the customer. The problem research includes, Has'thequality provided such as the health service already been suited well with the costumers need and expectationas well. What factors hinder and support in enhacing the quality of yhe health service. The research isqualitative using an interactive data analysis model (Miles and Huberman,1984). The results of research,RSUD Sidoarjo has managed to provide sufficiently qualified health services but it has not provided theservices which is based or oriented to customer (customer-oriented). Some supporting factors comprise,sufficiently qualified human resources, sufficient budget, facilities supporting services. Some hinderingfactors consist of, internal obstacles, less skilful human resources, the discomfort due to on-going buildingconstruction. The external hinders which comprise the awareness adn the understanding level of patientwill have a significant influence on her or his perspective in evaluating or judging the health service whichhospital offers.